Pasar Sepuran Di Mata Masyarakat Desa Pagerdawung Kecamatan Ringinarum Kabupaten Kendal - Noviafitri, Kartika Satya; Sabardilla, Atiqa (JURNAL DESTINASI PARIWISATA, 2023)
Surprise market is a culinary tour that is in great demand on weekend. One of the culinary destinations that are liked by all circles. This study aims to determine the potential of the Sepuran market in Pagerdawung Village, how the market attracts the attention of the local community so that it prefers the Sepuran market as a traditional market compared to modern markets such as supermarkets and online markets. The method used is descriptive qualitative method and data collection used is in depth interviews and observation. Research results Sepuran Market is the result of the development of traditional markets. The community's thinking continues to develop so that the Sepuran Market emerges as the fruit of the Pagerdawung community's creative thinking. Sepuran Market consists of various culinary delights. Sepuran Market has positive and negative impacts that complement its presence in Pagerdawung Village. In the modernization era, Pasar Sepuran cannot compete with modern markets. Apart from losing in terms of cleanliness, they also lost in terms of permits for buying and selling practices. Keywords: surprise market, traditional market, culiner